Effectiveness of Effleurage Massage in Reducing the Risk of Hospital-Acquired Pressure Injuries: Implications for Nursing Management in Geriatric Care - Reni Asmara; Tri Kurniati; Dhea Natashia; Harif Fadhillah; Muhammad Hadi (Jurnal Ners, 2026)
Hospital Acquired Pressure Injury (HAPI) is a local injury to the skin or tissue occurring during hospital care due to pressure, friction, or both. Effleurage massage is believed to improve blood circulation and reduce HAPI risk in geriatric patients. This study aimed to determine the effect of effleurage massage on HAPI risk in hospitalized geriatric patients. A quasi-experimental pretest-posttest non-equivalent control group design was employed with 34 geriatric patients, divided equally into intervention and control groups. Bivariate analysis used paired and independent t-tests, while multivariate analysis employed Repeated Measure ANOVA. Results showed that Braden Scale scores in the intervention group increased from 13.18 ± 2.038 to 20.71 ± 2.229 after 5 days of intervention (p < 0.001), indicating a significant reduction in HAPI risk. The control group showed no significant change. Multivariate analysis revealed significant effects of time, group, and interaction on HAPI risk reduction, with partial eta squared values of 0.649, 0.757, and 0.703, respectively. These findings confirm that effleurage massage is an effective preventive intervention to reduce HAPI risk in geriatric patients